Prognostic role of NRAS isoforms in Chinese melanoma patients. Issue 3 (June 2019) - Yan, Junya; Xu, Longwen; Yu, Jiayi; Wu, Xiaowen; Dai, Jie; Xu, Tianxiao; Yu, Huan; Guo, Jun; Kong, Yan
Abstract : Neuroblastoma rat-sarcoma viral oncogene homolog (NRAS) isoforms are expressed in melanoma tumor tissues, which have been described in Caucasian melanoma. However, the status and the clinical significance of NRAS isoforms in the Asian population have not been investigated on a large scale. We examined the expression levels of NRAS isoforms of 140 melanoma samples using quantitative real-time PCR. Furthermore, the relationship of mRNA expression of NRAS isoforms to clinicopathological characteristics and survival of patients was analyzed. Statistical analysis showed that NRAS isoform 2 expression was correlated with melanoma subtypes ( P =0.007), and NRAS isoform 4 expression was correlated with tumor thickness ( P =0.031) and clinical stage ( P =0.006). The median overall survival for patients with high expression of NRAS isoform 3 was significantly shorter than that for patients with low expression of NRAS isoform 3 ( P =0.007). In addition, high expression of NRAS isoform 5 was associated with a worse prognosis ( P =0.049 and 0.002 for overall survival and disease-free survival, respectively). Multivariate Cox regression analysis showed that high expression levels of NRAS isoform 3 and isoform 5 were independent poor prognostic factors for patients. Our results indicated that the mRNA expressions of NRAS isoform 3 and isoform 5 may be novel indicators of the prognosis of Chinese melanoma patients. Abstract : Supplemental Digital Content is available in the text.